Swot Analysis to Determine The Right Business Strategy - Nisa', Chanifatun; Sri Nuringwahyu; Chanafi, Ainul (International Journal of Entrepreneur and Business Administration, 2024)
This study aims to determine the internal and external factors of the company, the company's portfolio and determine the right business strategy at JAB Feed Animal Feed Factory. This type of research uses a sequential exploratory model and the method used is a mixed method or mixed method. The focus of this research is to analyze internal factors and external factors including: strengths, weaknesses, opportunities and threats that affect the JAB Feed Animal Feed Factory in determining the company's portfolio and determining business strategies. The data sources used are observations, questionnaires and interviews. In this study using 2 data analysis techniques, namely the qualitative data analysis technique used in this study using interactive Miles and Huberman. While quantitative analysis techniques use SWOT analysis. The data validity used in this research is source triangulation. The results showed that the internal factors of the JAB Feed Animal Feed Factory obtained a value of 0.75 while for external factors obtained a value of 1.03 and the company was in quadrant I position, this position indicates a strong and opportunity company/aggressive strategy, where an aggressive strategy means that the company must be able to take advantage of the company's strengths in maximizing opportunities from the company's external scope.